2018
DOI: 10.1007/s00401-018-1872-5
|View full text |Cite
|
Sign up to set email alerts
|

Non-Alzheimer’s contributions to dementia and cognitive resilience in The 90+ Study

Abstract: The diagnosis of Alzheimer's disease (AD) in the oldest-old is complicated by the increasing prevalence of age-related neurofibrillary tangles, plaques and non-AD pathologies such as cerebrovascular disease (CVD), hippocampal sclerosis (HS), aging-related tau astrogliopathy (ARTAG), as well as TDP-43 and Lewy pathology. The contribution of these non-AD pathologies to dementia and cognitive resilience is unclear. We assessed the level of AD neuropathologic change (ADNPC) and non-AD pathology in 185 participants… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
100
3
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 121 publications
(115 citation statements)
references
References 47 publications
(88 reference statements)
8
100
3
1
Order By: Relevance
“…Although we and others found that infarcts and small vessel disease (a term encompassing hyaline arteriolosclerosis) were related to cognitive impairment in younger and very old participants (2,9,20,21,37,50), it is important to note that we found an attenuation in the association between infarcts and cognitive impairment in very old participants that were not previously described (28,41). Very old participants with infarcts had more than 3 times the odds of cognitive impairment compared to older participants without infarcts; however the association was much stronger in younger participants with infarcts that showed an odds for cognitive impairment of almost 7 times.…”
Section: Prevalence Of Neuropathological Lesions and Their Associatiomentioning
confidence: 66%
See 1 more Smart Citation
“…Although we and others found that infarcts and small vessel disease (a term encompassing hyaline arteriolosclerosis) were related to cognitive impairment in younger and very old participants (2,9,20,21,37,50), it is important to note that we found an attenuation in the association between infarcts and cognitive impairment in very old participants that were not previously described (28,41). Very old participants with infarcts had more than 3 times the odds of cognitive impairment compared to older participants without infarcts; however the association was much stronger in younger participants with infarcts that showed an odds for cognitive impairment of almost 7 times.…”
Section: Prevalence Of Neuropathological Lesions and Their Associatiomentioning
confidence: 66%
“…When we examined the association of neuropathological lesions with cognitive impairment, we found higher odds of impairment with increasing NFT BB stages, chronic infarcts and hyaline arteriolosclerosis in both age groups. Indeed, high NFT BB stages were associated with dementia in several studies with very old participants (15,28,37,46), while neuritic plaque burden has been inconsistently associated with dementia (6,37,38,41,50). Interestingly, several studies pointed to an attenuation of the association between AD neuropathological changes and dementia in the very old (19,21,28,41).…”
Section: Prevalence Of Neuropathological Lesions and Their Associatiomentioning
confidence: 99%
“…adding mathematical models that describe how molecular changes alter population activity -so called cause--and--effect models. We will focus here on the disrupted inhibitory function of interneurons and consecutive hyperexcitability caused by Abeta -while we are aware of various other factors with potential roles for AD aetiology, such as vascular changes (19--21), neuroinflammation (22--25), genetics (26--28), environmental factors (29,30) and concomitant proteinopathies others than Abeta pathology (31,32). Beside Abeta there is a second molecular hallmark associated with the pathogenesis of AD: the phosphorylated Tau 'tubulin--associated unit' protein (8,33,34) which contributes to microtubule stability in the neural cytoskeleton (34).…”
mentioning
confidence: 99%
“…with BAN--2401 (42). A relevant percentage of clinically diagnosed AD patients show additional brain pathologies beside Abeta and Tau in autopsy (32). Even in the cases of neuropathological AD diagnosis (i.e.…”
mentioning
confidence: 99%
“…It is possible that these tauopathies may often be overlooked against the background of severe AD neurofibrillary pathology. Reports from centers that specifically look for argyrophilic grains and aging-related tau astrogliopathy (ARTAG) find AD comorbidity rates up to 40% for both [143][144][145][146][147][148][149][150]. The classical conditions in this group, including progressive supranuclear palsy (PSP), corticobasal degeneration (CBD) and Pick's disease, are much less prevalent, although PSP may be considerably more common than previously realized due to low clinical sensitivity for the diagnosis [143,[151][152][153][154][155][156][157][158].…”
Section: Introductionmentioning
confidence: 99%